SELF INSTRUCTION AMONGST CHINESE HIP-HOP MUSICIANS: REFLECTIONS ON INFORMAL MUSIC LEARNING IN CHINA - LI, Mengdi; A. MARSHALL, Nigel (Problems in music pedagogy, 2024)
Academic studies of music education in the subject of hip-hop have grown over the last several decades due to the genre's growing appeal among young people worldwide. In the Chinese context, hip-hop music was developed only in the last few years. Although experts in a variety of fields such as educational and musical areas have begun to pay more attention to hip-hop music in the last five years, there is almost no research on the learning patterns of hip-hop musicians in the Chinese context. This study examined the musical learning experiences of eight Chinese hip-hop musicians by using semi-structured interviews to understand more about their learning styles, learning pathways, and attitudes to school music instruction. Outcomes suggested that Chinese hip-hop performers predominantly learned music through informal music learning practices, including listening, imitation, individual practice, and independent composition. Additionally, the research identified a positive and mutually reinforcing relationship between informal music education and music education in schools. Finally, the paper compares and evaluates the current findings with prior scholarship on informal music learning and school music education, and made recommendations for school music education and future academic research in the Chinese setting.